Perancangan Maskot sebagai Identitas Visual Klinik Fan Vet Petcare Gresik - Vandhu Hidayat; Masnuna; Pungky Febi Arifianto (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2024)
A mascot is a character or form that can be formed from humans, animals, or objects that are used as figures that are considered to depict and/or reflect the image of a company. Mascots have an important role in the visual identity of a company because they can make promotional activities more attractive. In a promotional activity, Mascots can interact with the audience in their way which can make the atmosphere more lively and interesting. The design of the mascot for the Fan Vet Petcare Gresik clinic was carried out to strengthen the visual identity of a veterinary clinic so that it can attract more attention from animal lovers. The Fan Vet Petcare Gresik Clinic quite educational content as well as holding promotions and campaigns for the good of animals that are still not well cared for on the streets and pets, so the presence of a mascot for the Fan Vet Petcare Gresik Clinic is hoped that it can improve the activities carried out by the clinic. Fan Vet Petcare Gresik was delivered well and interestingly. The data analysis process and techniques use qualitative methods through the preparation and design creation stages. The data obtained will be analyzed descriptively to obtain conclusions as a reference for finding solutions to existing problems. This mascot design aims to be the visual identity of the Fan Vet Petcare Gresik Veterinary Clinic and become its visual identity in promoting or campaigning for positive activities for animal lovers. In designing the mascot design, there will be several mascot design implementations with promotional design campaigns or educational content on social media.